Comparison of Retention of Clasps Made of Different Materials Using Three-Dimensional Finite Element Analysis - Jaggari Chandrakanth Reddy; Sarath Babu Chintapatla; Naveen Kumar Srikakula; Rajesh Kumar Reddy Juturu; Shameen Kumar Paidi; Satyendra Kumar Tedlapu; Padmakanth Mannava; Rukhaiya Khatoon (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Retention and esthetics are believed to play a crucial role in deciding the success of removable partial dentures. Aim: To compare retention of acetal resin and cobalt–chromium clasps. Materials and Methods: A finite element model was designed with an edentulous space between mandibular right second premolar and second molar. Occlusal rests were placed on distal fossa of the second premolar and mesial fossa of second molar. An undercut depth of 0.01inch was created on the mesiobuccal surface of the premolar and distobuccal surface of second molar. Three dimensional finite element model of clasp assembly was designed and assigned with the properties of two different materials namely acetal resin and cobalt–chromium in successive steps. A horizontal bar was constructed between the occlusal rests of the prosthesis. Later, variable amount of dislodging force, in increasing order, was applied at the centre of the horizontal bar and the force at which the clasp arm gets dislodged was noted with respect to each of the material. The obtained values were noted and then subsequently analyzed. Results: The amount of force required to dislodge acetal resin and cobalt–chromium clasps was found to be 0.02N and 2N respectively. Conclusion: The results obtained suggested that acetal resin clasp exhibited less retentive force than cobalt–chromium clasps.